Carbenoxolone mitigates extensive fibrosis formation in PLP-induced EAE model and multiple sclerosis serum-exposed pericyte culture - Ucar, Ege Anil; Ozkan, Esra; Shomalizadeh, Narges; Sekerdağ-Kilic, Emine; Akpunar, Fatmanur; Sapanci, Selin; Kesibi, Judy; Ozler, Ceyda; Bilgez, Alara Su; Gursoy-Ozdemir, Yasemin (Frontiers in Cellular Neuroscience, 2024)
Multiple sclerosis (MS) is one of the most common causes of disability in young adults.Nearly, 85% of MS cases start with attacks and remissions, classified as relapsing-remitting multiple sclerosis (RRMS). With repeating attacks, MS causes brain-spinal cord atrophy and enhanced disability as disease progresses. PLP-induced EAE is one of the most established models for pathophysiology and treatment of RRMS. Recent studies demonstrated the possible role of pericytes in perivascular and intra-lesional fibrosis in PLP-induced EAE, whose importance remains elusive. Hence, we have investigated the possible role of pericytes in fibrosis formation and amelioration with a hemichannel blocker, Carbenoxolone (CBX). PLP-induced experimental autoimmune encephalitis (EAE) model is used and the effect of CBX is investigated. Clinical scores were recorded and followed. Perivascular Collagen 1 and 3 accumulations were demonstrated as markers of fibrosis in the spinal cord. To delineate the role of pericytes, human brain vascular pericytes (HBVP) were incubated with the sera of three MS patients to induce in-vitro MS model and the fibrosis formation was investigated. In the PLP induced in-vivo model, both ICV and IP CBX have significantly mitigated the disease progression followed by clinical scores, demyelination and fibrosis, suggesting that hemichannels have a role in the disease process and it may be a potential novel therapeutic option.CBX mitigated MS-serum-induced fibrosis in the HBVP cell culture showing that perivascular pericytes have a role in fibrotic extracellular matrix accumulation and disease progression. This effect may be through its antifibrotic actions by blocking hemichannels and especially targeting progressive atrophy and disability.